Pediatric autoimmune encephalitis: a review - Shah, Bipesh K.; Singh, Arun K. (International Journal of Contemporary Pediatrics, 2024)
Autoimmune encephalitis has been an emerging disease in the pediatric age group for the last few years. It is of utmost importance to recognize the disease for the timely initiation of immunotherapy. The antibody-mediated encephalitis should be considered in the differentials apart from vasculitic, metabolic encephalopathy after ruling out bacterial, viral, tubercular, parasitic, and rickettsial causes. It can even coexist with herpes encephalitis in a quarter of the cases. The prodromal symptoms and progression to psychiatric, memory, speech disturbance, movement disorder, altered mental status, dysautonomia, and seizures within a span of a month characterize the disease. The approach to diagnosis involves various antibody testing in serum and cerebrospinal fluid along with brain imaging and electroencephalography. Early treatment with steroids, intravenous immunoglobulin, and plasmapheresis leads to better outcomes. A literature search was made using keywords in the Google Scholar and Pubmed databases before January 2024. The collected materials were reviewed for appropriate titles and content focusing on diagnosis and management. The article aims to provide a comprehensive review regarding the differential diagnosis and management of autoimmune encephalitis in children.